2021
DOI: 10.1177/02762366211021076
|View full text |Cite
|
Sign up to set email alerts
|

Communication in the Time of COVID-19: An Examination of Imagined Interactions and Communication Apprehension During the COVID-19 Pandemic

Abstract: As people all over the world continue to adjust to the new normal presented to them by COVID-19, they must adjust to the social restrictions that have been enforced. These restrictions include shelter-in-place and work-from-home orders that severely limit the face-to-face interactions that were considered a norm in many peoples’ lives (e.g., speaking with the grocer, hair stylist, etc.). As individuals adjust to these changes, their communication behaviors must adapt as well. This study seeks to determine how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This means that students in this study were more apprehensive about communicating with interpersonal speaking than in the other subscales, which might give insight into how interpersonal conversation was affected after the COVID-19 lockdown [ 37 ]. During the COVID-19 pandemic, individuals relied more on social media interactions rather than interpersonal communication, and this could be the reason behind the decreased interpersonal speaking [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This means that students in this study were more apprehensive about communicating with interpersonal speaking than in the other subscales, which might give insight into how interpersonal conversation was affected after the COVID-19 lockdown [ 37 ]. During the COVID-19 pandemic, individuals relied more on social media interactions rather than interpersonal communication, and this could be the reason behind the decreased interpersonal speaking [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol has been shown to be a coping mechanism for dealing with psychological stress in stigmatized individuals (Hatzenbuehler et al, 2011;Pachankis et al, 2018), as well as a disinhibiting factor in the field of first dates (Goldman & Roehrich, 1991;Mongeau et al, 2007). As discussed previously, one of the core functions of IIs is selfunderstanding; research on IIs and coping has found them to be a powerful instrument for making sense of unexpected communication / behavior (Berkos et al, 2001) and reducing fear (Gotcher & Edwards, 1990) as well as communication apprehension (Sealy, 2021). The proposed hypothesis to test the relationship between IIs and the perceived stigma associated with using online dating apps follows:…”
Section: Iis and Online Datingmentioning
confidence: 99%
“…Future cognitive work should consider how these individuals plan for interactions, as well as how they are able to handle their loneliness and related experiences. This may be a particularly important group to study considering the COVID-19 pandemic context specifically, especially in light of other findings related to the use of IIs and communication apprehension during COVID-19 (Sealy, 2021). What are these individuals’ coping mechanisms when mental imagery is unavailable to them?…”
Section: Discussionmentioning
confidence: 99%
“…The compensation function of IIs is of particular interest in this context, as people globally have experienced an increase in separation from others and a decrease in the amount of in-person communication that is possible (Vendemia & Coduto, 2022). Yet research exploring relationships between IIs and communication apprehension during COVID-19 suggests that individuals may be experiencing fewer IIs as they have fewer social interactions (Sealy, 2021). As this work has mostly focused on workplace-related IIs, it is worth expanding understanding of if and when IIs are used during a time of physical distancing from others.…”
Section: Literature Reviewmentioning
confidence: 99%